(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Present experiment was laid out at Agriculture farm, Rama University Kanpur during 2020-21 1.: Plant Population, Plant height (cm), Number of branches plant-1 , 2. Post harvest studies: Plant character, Number of siliquae plant-1 , Number of seeds siliqua-1 , Siliqua length (cm), Seed weight / plant, Weight of Siliqua/plant, (ii) Yield Character, Biological yield, Seed yield (q ha-1 ), Stover yield (q ha-1 ) (iii). Test weight (g), iv). Harvest index, Economics:- Benefit: cost ratio. Gross income, Net income, Cost of cultivation The superior plant height and plant population registered from plot which was treated T8 (75% RDF + FYM 20 t ha-1 + Azotobacter +PSB). In similar lines the grain and straw yield was also recorded highest for the same. The experiment was laid out in Randomized Block Design, the experiment consist of 8 treatments with three Replications